DEVELOPMENT OF JUWANA HERITAGE IN MATHEMATICS ANDROID APPLICATION INTEGRATED WITH PROBLEM-BASED LEARNING ASSISTED BY ADOBE ANIMATION TO IMPROVE MATHEMATICAL PROBLEM SOLVING SKILLS - Detalia Noriza Munahefi; Alifia Sabila Al-qonita (MATEMATIKA DAN PEMBELAJARAN, 2025)
Mathematical problem-solving skills need to be developed to achieve the SDGs, specifically in quality education. However, the results of the 2022 PISA (Philosophy of Mathematics) show that the problem-solving ability of students in Indonesia is relatively low. Innovation is needed to improve problem-solving abilities by developing an Android application integrated with Problem-Based Learning (PBL) with cultural nuances. The study aims to develop an Android application, "Juwana Heritage in Mathematics," integrated with PBL assisted by Adobe Animate. Research and Development (R&D) with the ADDIE model (Analyze, Design, Develop, Implementation, and Evaluation) is the research method. Data sourced from validation questionnaires, practicality questionnaires, student response questionnaires, and problem-solving ability tests. The validity test results were 89.35% in the very valid category. The practicality test results were 87.7% in the very practical category. Test the effectiveness of the application through t-tests, z-tests, and proportion tests. The results of statistical tests show that (1) the average mathematical problem solving ability of students with the Juwana Heritage in Mathematics application integrated with PBL reached a minimum completion of 80, (2) the proportion of students' problem solving ability with the Juwana Heritage in Mathematics application integrated with PBL that had reached completion was more than 75%, (3) the average mathematical problem solving ability of students with the Juwana Heritage in Mathematics application integrated with PBL was higher than students with PBL (4) the proportion of students' completion with the Juwana Heritage in Mathematics application integrated with PBL was higher than students with PBL and (5) the increase in problem solving ability in students with the Juwana Heritage in Mathematics application integrated with PBL was higher than students with PBL.